Regular and Young Investigator Award Abstracts 2020
DOI: 10.1136/jitc-2020-sitc2020.0030
|View full text |Cite
|
Sign up to set email alerts
|

30 NLR (neutrophil lymphocyte ratio) and PLR (platelet lymphocyte ratio) changes as a predictor of eventual treatment failure and death on nivolumab therapy in renal cell carcinoma

Abstract: BackgroundElevated baseline neutrophil lymphocyte ratios (NLR) are now well established as a poor predictor of survival in renal cell carcinoma (RCC) and other cancers. Platelet Lymphocyte Ratios (PLR) have also recently shown similar effects. Despite these findings, the practical use of these ratios is still somewhat limited. We have previously shown that higher NLRs may be associated with increased concentrations of myeloid derived suppressor cells (MDSC). We hypothesized that increases in NLR or PLR (NLR/PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…After examining titles and abstracts, 19 studies were identified. A total of seven studies had insufficient data following a full-text review, leaving 12 records included according to the eligibility criteria (Figure 1) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The literature search was performed by two investigators, and any disagreements between them were settled by consensus.…”
Section: Literature Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…After examining titles and abstracts, 19 studies were identified. A total of seven studies had insufficient data following a full-text review, leaving 12 records included according to the eligibility criteria (Figure 1) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The literature search was performed by two investigators, and any disagreements between them were settled by consensus.…”
Section: Literature Characteristicsmentioning
confidence: 99%
“…The total number of patients from the included studies was 1,275, ranging from 37 to 404 cases per trial. In total, 9 studies were from Western countries, including the USA (17)(18)(19)(20)(21)28), Italy (24,27), and France (25). Another three were from Japan (22,23,26).…”
Section: Literature Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations